2005
DOI: 10.1017/s0025315405010787h
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning, bioavailability and effects of oestrogens and xeno-oestrogens in the aquatic environment

Abstract: This review provides insights into the distribution and impact of oestrogens and xenooestrogens in the aquatic environment and highlights some significant knowledge gaps in our understanding of endocrine disrupting chemicals. Key areas of uncertainty in the assessment of risk include the role of estuarine sediments in mediating the fate and bioavailability of environmental (xeno)oestrogens (notably their transfer to benthic organisms and estuarine food chains), together with evidence for endocrine disruption i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 217 publications
0
42
0
3
Order By: Relevance
“…It may be that this is the 'normal' condition for these clams; however, since the initial finding, we have sampled at least six sites in other estuaries, where none of the population displays intersex. It is possible, therefore, that (xeno)oestrogens may be responsible: ovotestis in fish has been conclusively linked to the presence of endocrine disrupting compounds (Purdom et al 1994;Jobling et al 1998;Bateman et al 2004), and there is emerging evidence that sex steroids play a role in the regulation of reproduction in bivalve molluscs (for review of relevant literature, see Langston et al 2005). Potential sources in the Avon include effluent from an upstream sewage treatment works (a potential source of steroid oestrogens and other oestrogenic chemicals) or perhaps, owing to the rural nature of the estuary, agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that this is the 'normal' condition for these clams; however, since the initial finding, we have sampled at least six sites in other estuaries, where none of the population displays intersex. It is possible, therefore, that (xeno)oestrogens may be responsible: ovotestis in fish has been conclusively linked to the presence of endocrine disrupting compounds (Purdom et al 1994;Jobling et al 1998;Bateman et al 2004), and there is emerging evidence that sex steroids play a role in the regulation of reproduction in bivalve molluscs (for review of relevant literature, see Langston et al 2005). Potential sources in the Avon include effluent from an upstream sewage treatment works (a potential source of steroid oestrogens and other oestrogenic chemicals) or perhaps, owing to the rural nature of the estuary, agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…the bioavailability may increase for some filter feeders as a result of uptake from SPM or sediments (Langston et al, 2005;Wenzel et al, 2004). Typical EDCs are found to have high affinity for particulate matter and to exhibit low degradation rates in anoxic conditions (Gong et al, 2012;Jin et al, 2008).…”
Section: Environmental Implicationmentioning
confidence: 99%
“…Typical EDCs are found to have high affinity for particulate matter and to exhibit low degradation rates in anoxic conditions (Gong et al, 2012;Jin et al, 2008). Thus sediments can be either directly involved in aquatic organism exposure to EDCs or may subsequently act as a secondary source, particularly to benthic infauna as a result of a combination of processes including direct ingestion, slow release by diffusion at the sediment/water interface, and sediment resuspension and transport during high water flows (Langston et al, 2005). It was found that sediment-associated EDCs could become bioavailable to aquatic biota and induce endocrine responses, and sediment characteristics such as particle size, composition, organic carbon source, form and age, etc., could influence the bioavailability and endocrine-disrupting effects of these compounds (Sangster et al, 2014;Langston et al, 2005).…”
Section: Environmental Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…EDCs are lipophilic (tending to dissolve in lipids) and continue to persist in the environment due to production abroad, long half-lives, and continued dispersal into the natural environment (Colborn et al, 1993). In particular, estrogenic EDCs and their metabolites bioaccumulate and biomagnify in environments (Colborn, 1998;Langston et al, 2005) and have the potential to interact deleteriously with resident biota.…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 99%